An estimation and decomposition of the government investment multiplier - Marius Clemens; Claus Michelsen; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
We construct a narrative instrument for government investment from official records in Germany. Using structural vector autoregressions, we document a significant crowding-in of private investment and an output multiplier of roughly 2. Then, we match a New Keynesian dynamic stochastic general equilibrium model to the empirical responses, and we decompose the multiplier into three channels. Public investment reduces private investment costs in the short run, it increases the production capacity in the medium run, and it generates demand effects along the production network. We find a similar multiplier in other euro area countries, using an indirect instrumental variable strategy.
Keywords: E62; E65; H54; 330; Fiscal policy; public investment; structural vector autoregression; instrumental variable; general equilibrium model; Germany